Introduction to public health - Goldsteen, Raymond L.; Goldsteen, Karen ;Graham, David G. (New York : Springer Publishing Company, 2011)
" ... this introductory textbook provides a comprehensive understanding of the unique history, economics, orientation, function, activities, and mission of public health. This concise reference describes the successes and failures of the public health care system, giving students a clear picture of the current status of the health care industry. Introduction to Public Health also identifies new public health initiatives, including evidence-based practices, accreditation and credentialing programs, and more. Also discussed are critical, up-to-the-minute issues, such as health disparities, infectious and chronic disease prevention, and injury prevention. The book also presents real-life public health vignettes in every chapter to help conceptualize the complex set of factors that affect health. Key topics discussed: [1] The origins of the modern day public health system, [2] Health promotion, [3] Primary, secondary, and tertiary prevention, [4] The determinants of health, [5] Federal, state, and local public health systems, [6] The financing of public health, [7] Infectious disease prevention, [8] Chronic disease prevention, [9] Public health system performance and measurement, [10] Healthy People 2010 and other key public health initiatives."--Publisher.
Origins of public health -- Organization and financing of public health -- Infectious disease control -- Injuries and noninfectious diseases -- Public health system performance -- Public health : promise and prospects.
Includes bibliographical references and index.
Keywords: PUBLIC HEALTH